Language Learning, Cultural Adaptation, and Student Mental Wellbeing: Case of MEXT scholars to Japan (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Economic liberalization in India in the early 1990s, along with rising living standards, has significantly increased the number of Indian nationals traveling abroad for employment and higher education.Students pursuing education in foreign universities often experience considerable psychological stress and emotional challenges. These stresses arise from several factors, including: (1) separation from family and familiar social networks, (2) adjustment to a new geopolitical and cultural environment, (3) adaptation to unfamiliar academic systems and expectations, and (4) the necessity of independent living.Each year, seven to eight students from the Japanese Language Department of Tilak Maharashtra Vidyapeeth (TMV) travel to Japan for a one-year study program under the scholarship offered by the Ministry of Education, Culture, Sports, Science and Technology of Japan (MEXT). Despite having prior knowledge of the Japanese language and culture, these students encounter many of the aforementioned challenges, particularly during the initial stages of their stay.This study is based on a questionnaire survey conducted with nine MEXT scholars. The objectives of the study are: (1) to understand the challenges faced by students and the coping mechanisms they adopt, (2) to identify measures that can better prepare students prior to their departure for Japan, and (3) to explore how TMV’s Japanese Language Department can support students’ mental well-being throughout their stay abroad.The findings highlight a range of psychological, lifestyle-related, and academic issues experienced by the students.This paper proposes the following practical measures that TMV’s Japanese Language Department can implement to help minimize the stress experienced by MEXT scholars during their time in Japan.• Create a guidebook about life in Japan, 2. Arrange an orientation session, 3. Assign a session on writing a research paper,4. Assign a faculty mentor to each student, 5. Arrange meetings, 6. Arrange a session on mental health